2020
DOI: 10.1007/s42452-020-03377-8
|View full text |Cite
|
Sign up to set email alerts
|

Lattice Boltzmann simulation of magneto-hydrodynamic double-diffusive natural convection in an enclosure with internal heat and solute source using nanofluids

Abstract: Magneto-hydrodynamic double-diffusive natural convection in a cavity is numerically investigated in the present work. Al 2 O 3 , Cu, and Ag based nanofluids in a square cavity with a thermal and solute source in the center, and uniform magnetic field are considered. The Patel model is employed to estimate the thermal conductivity of applied nanofluids, and the numerical calculation is based on the implementation of the lattice Boltzmann method and utilizing the standard D 2 Q 9 model to study the heat transfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Results showed that the longer baffle is always more effective with proper positioning. Ghasemi et al 41 and Afzalabadi et al 42 all investigated the influence of magnetic field on the natural convection of nanofluids by lattice Boltzmann method, and the results presented that magnetic field has a negative influence on thermal performance. Mliki et al 43 simulated the influence of Ha on the natural convection of nanofluids in a linearly/sinusoidally heated cavity by lattice Boltzmann method, and it was indicated that thermal performance decreases with Ha .…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that the longer baffle is always more effective with proper positioning. Ghasemi et al 41 and Afzalabadi et al 42 all investigated the influence of magnetic field on the natural convection of nanofluids by lattice Boltzmann method, and the results presented that magnetic field has a negative influence on thermal performance. Mliki et al 43 simulated the influence of Ha on the natural convection of nanofluids in a linearly/sinusoidally heated cavity by lattice Boltzmann method, and it was indicated that thermal performance decreases with Ha .…”
Section: Introductionmentioning
confidence: 99%